The Harm in Kratom. (August 2017) - Drago, Joshua Z.; Lane, Bennett; Kochav, Jonathan; Chabner, Bruce
Abstract : A case of severe hepatic toxicity associated with the use of kratom, a plant derivative increasingly used as a psychostimulant, is discussed.